A two-dimensional model for the subthreshold swing of short-channel double-gate metal-oxide-semiconductor field effect transistors with a vertical Gaussian-like doping profile - Dubey S.; Tiwari P.K.; Jit S. (My University, 2025)
An analytical two-dimensional (2D) model for the subthreshold swing of the short-channel double-gate (DG) MOSFET with a vertical Gaussian-like doping profile is presented in this paper. The 2D potential function obtained by solving the 2D Poisson's equation by using the evanescent mode analysis has been used to formulate the subthreshold current. The concept of the effective conduction path effect of uniformly doped DG MOSFETs has been extended to the nonuniformly doped DG MOSFETs to obtain the subthreshold swing variations against doping profile parameters as well as device parameters of the present device. The results of the model show excellent matching with the numerical simulation data obtained by using the commercially available ATLASTM, a two-dimensional device simulator from SILVACO. © 2011 American Institute of Physics.